Therapeutic value of selective lymphadenectomy in interval debulking surgery for stage IIIc and IV epithelial ovarian cancer. Issue 4 (7th March 2019) - Song, Nan; Gao, Yunong
Abstract : Objective: The role of selective lymphadenectomy at the time of interval debulking surgery in patients with advanced ovarian cancer remains a topic of debate. This study aimed to evaluate the value of selective lymphadenectomy during interval debulking surgery in patients with radiologic evidence of lymph node metastasis at initial diagnosis that ultimately become negative on imaging after neoadjuvant chemotherapy. Methods: A retrospective analysis including patients with stage IIIC–IV epithelial ovarian cancer and suspicious pelvic or para-aortic lymph node metastasis by imaging at diagnosis that resolved after neoadjuvant chemotherapy. The study was conducted from January 1996 to June 2016 with R0 interval debulking surgery. The patients with disease progression after neoadjuvant chemotherapy were excluded. Suspicious metastatic lymph nodes at initial diagnosis by computed tomography/magnetic resonance imaging were excised by selective lymphadenectomy. Survival curves were constructed by the Kaplan-Meier method, and a multivariate analysis was performed using Cox regression. Results: There were a total of 330 patients included in the analysis. Selective lymphadenectomy of suspicious nodes (Group 1) was performed in 145 patients. Systematic lymphadenectomy (Group 2) was performed in 118 patients. Sixty-seven patients did not undergo lymphadenectomy (Group 3). There were no significant differences in clinicopathologic features among the groups. Median progression-free survival was 28, 30.5, and 22 months in Groups 1, 2, and 3, respectively (log-rank, p=0.049). No-lymphadenectomy was an independent factor affecting progression-free survival (Cox analysis, HR=1.729, 95% CI 1.213 to 2.464, p=0.002), with no difference between Groups 1 and 2 (Cox analysis, HR=1.097, 95% CI 0.815 to 1.478, p=0.541). Median overall survival was 50, 59, and 57 months in Groups 1, 2, and 3, respectively (Cox analysis, p=0.566). Patients who underwent selective lymphadenectomy had lower 1-year frequencies of lower extremity lymphedema and lymphocysts than those with systematic lymphadenectomy (6.2% vs 33.1%, p<0.001, and 6.2 % vs 27.1%, p<0.001, respectively). Conclusions: Extent of lymphadenectomy (systematic or selective) had no significant impact on progression-free survival or overall survival. In addition, the risks of lower extremity lymphedema and lymphocysts were lower in patients who underwent selective lymphadenectomy.